RADICALISM IN THE MODERN WORLD: SOCIAl AND POLITICAL ANALYSIS - Требін, Михайло Петрович (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2019)
Problem setting.The relevance of the problem of the study is determined by the fact that in modern conditions radicalism is an integral component of the political life of many countries, manifesting itself in the activities, values of the ruling and opposition elites, as well as ordinary citizens. Being a multifaceted phenomenon, in the age of globalization, it is transformed and modified, taking on different types and forms, corresponding to new civilizational challenges and risks. Recent research and publications analysis. The phenomenon of radicalism is constantly in the field of view of scientists. But in the last two decades alone, dozens of books and hundreds of articles have been written on this topic, and several encyclopedias have been published exploring the phenomenon. Among scholars who study the nature, nature, forms and methods of combating radicalism, such researchers as B. Balleck, B. Barnes, K. Bos, J. Weitzdörfer, A. Goings, O. Grishin, V. Davidov, D. Johnson, M. Cohen, I. Lopushansky, D. Needham, J. Radwani, H. Rahman, S. Samoilov, V. Plotnikov, R. Snyder, I. Shegaev and others. Much attention was paid to the study of radicalism by Ukrainian scientists, such as S. Avdeyev, V. Antipenko, O. Bardin, V. Yemelyanov, V. Krutov, L. Levchenko, V. Lipkan, V. Mandragelya, O. Panfilov, V. Smolyanuk , M. Cherkas and others. [24-26]. But because of the complexity, the variability, the multiplicity of this phenomenon, its social and political danger, radicalism needs to be constantly considered and monitored. Paper objective. The purpose of the article is to investigate the phenomenon of radicalism and its main manifestations in modern society. Paper main body. The term “radicalism” originated in England at the end of the XVIII century. In the nineteenth century it has spread in continental Europe and has marked social and political and philosophical reflections focused on social, political, economic and cultural transformations and relevant reform practices. The sources of radicalism are the unfavorable socio-economic and political environment, ideological and ideological ideas, man-made and environmental threats, spiritual factors, socio-psychological attitudes and personality characteristics, internalized behavior and other factors. There are two main components of radicalism. First, it is the focus on a radical transformation of society, that is, its ideal is fundamentally (or at least very, very substantially) different from existing society. Secondly, radicalism is characterized by a commitment to decisive measures, methods, ways of transformation. Nowadays, the word “radicalism” means a way of thinking and a related pattern of behavior, characterized by: fundamentalism strict adherence to the requirements of any doctrine (religious, political, philosophical, etc.); a utopian view of the possibility of building a society in which the main types of social evil will be eradicated; revolutionism recognizes the inevitable drastic and violent change in existing social relations, the rule of law that enshrines them. The first element of radicalism establishes the essence of the world and the cause of inconsistency with its existing social relations. The second element points to the social ideal that society should strive for. The third element reveals the method of achieving the ideal. In other words, the three basic elements of radicalism answer the questions “what”, “why” and “how” to change in social life. In addition, radicalism is characterized by the absolutization of “simple” solutions to complex and multifaceted social, political, economic, interethnic, religious, environmental and other problems, the justification and idealization of violence as an “effective” means of direct and immediate action, thereby the illusory hope of overcoming social political helplessness, lack of tolerance and readiness for dialogue and compromise. The main types of radicalism are analyzed. Successfully combating radicalism can only be rooted in tolerance, supporting intercultural, inter-religious and inter-ethnic dialogue in society, forming the ideologem of anti-radicalism, political and legal culture of a truly democratic, legal, social society of European type. Only a comprehensive approach that combines the study of ideology and practice of radicalism with the conduct of information and education campaigns by public institutions, the media, all civil society, social, economic and political reforms to further democratization and liberalization of all spheres of life and quality of life, raising the quality of life , empowerment of all social groups, especially disadvantaged and marginalized groups, ensuring equal inter-denominational and inter-ethnic dialogue gu, joint efforts at the regional and global level, will give a real chance to minimize the manifestations of radicalism in modern society. It is impossible to destroy radicalism, but it is quite possible to minimize its destructive manifestations. Conclusions of the research. Radicalism is quite widespread in the modern world today. The actualization of these or other forms radicalism depends on the specific historical conditions and tasks facing the country and the respective socio-political forces and their location. The formation of a paradigm of anti-radicalism in society and its spread among the majority of the population is possible by overcoming the violence, destructiveness, irrationality and utopianism of the modern world.